1990
DOI: 10.1111/j.1467-6486.1990.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Tactical Factors in the Project Implementation Process

Abstract: It has been a well-recognized axiom in project management research that the project implementation process can be greatly facilitated by addressing a variety of project critical success factors. It is argued here that critical factors often fall into two distinct sub-groups: those related to initial project planning and those concerned with subsequent tactical operationalization. A field study was conducted to explore changes in the perceived importance of project planning and tactical factors across four stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 21 publications
4
109
0
10
Order By: Relevance
“…Common to these frameworks is a distinction between more or less planned styles of implementation [36,37]. A planned or rational style of implementation tends to be top-down and hierarchical, involving the use of pre-prepared action plans, performance monitoring, and review processes [31,38,39]. By contrast, an unplanned or incremental style of implementation is more bottom-up and less hierarchical, with staff deeply involved in adjusting and amending new practices as they are being introduced.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Common to these frameworks is a distinction between more or less planned styles of implementation [36,37]. A planned or rational style of implementation tends to be top-down and hierarchical, involving the use of pre-prepared action plans, performance monitoring, and review processes [31,38,39]. By contrast, an unplanned or incremental style of implementation is more bottom-up and less hierarchical, with staff deeply involved in adjusting and amending new practices as they are being introduced.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Some others have adopted a different approach and decided to empirically test the impact of these frameworks and of their success factors (e.g. Pinto and Prescott, 1990;Miller, 1997;Bauer et al, 2005;Bockmühl et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to evaluate participants in DBES projects against project success factors in order to identify key focus areas. Project success factors often fall into two groups: project planning and subsequent tactical operations, or implementation [1]. In previous research, the project design phase was found to have a great impact on overall project quality [2].…”
Section: Introduction: Motivation Of This Study and Its Aimsmentioning
confidence: 99%